Evaluación de la viabilidad de semillas de maíz (zea mays l.) mediante pruebas de tetrazolio y espectroscopía de infrarrojo (ft-nir). - Quezada Mendoza, Ariana Geanella (Machala : Universidad Técnica de Machala, 2019)
Within the world production of grains and cereals (rice, wheat, barley, etc.) corn (Zea mays L.) represents 40%, countries such as the United States (37%) and China (23%) are the highest grain production with yields of 10 and 6 t / ha respectively. Ecuador is among the top 50 world producers of this, being a crop of high significance is produced in 21 of the 24 provinces which its production is concentrated in the provinces of Los Rios, Guayas, Manabi and Loja, the importance of this research lies in the little research that generates information on how to conserve our seeds without losing their viability and genetic vigor, as well as breeding programs that generate genetic variability of superior agronomic characteristics. The present research was carried out in the "Santa Inés" Experimental Farm belonging to the Academic Unit of Agricultural Sciences of the Technical University of Machala (UTMACH), located in the Parroquia El Cambio, Cantón Machala. The objective was to evaluate the percentage of viability and germination of corn seeds through tetrazolium tests and infrared spectroscopy (FT-NIR). The experimental work was carried out completely at random, using nine accessions with two study factors (viability evaluation methods (Tetrazolium and NIR) and variety) with 3 repetitions. Feasibility tests were carried out in the laboratory using an NIR SCIO device to scan the seeds before germinating them, generating an absorbance curve for each seed, then the same seeds are placed to germination and using the Tetrazolium method the staining of the embryo of each seed is observed, the readings are made after 24 hours, the data obtained in the laboratory were submitted to a statistical test Factorial Variance Analysis and Tukey at 0.05 through the program Statistical Pasckage of the Social Sciences (SPSS), the data obtained in the laboratory were submitted to a statistical test Factorial Variance Analysis and Tukey at 0.05 through the program Statistical Pasckage of the Social Sciences (SPSS). Between the two methods, the lowest cost, without destroying the seed and of easy manipulation by means of an intelligent telephone is the NIR, achieving 100% positive results as far as viability and vigor of seeds; the Tetrazolio method is a reliable test that in the same way has effective results but the cost is superior and above all destroys the seed to carry out the evaluation. From the results obtained it was determined that there is no significant difference between varieties of corn according to their storage time which this medium did not influence. The varieties V1A, V2A, V3A that contain a humidity level of 5.5% presented less viability as for the varieties V1B, V2B, V3B, V1C, V2C, V3C that obtained lower humidity (5%), but higher percentage of viability. The tetrazolium method presented an average of 67.11 and the NIR method an average of 68.15 so there are no significant differences between the two methods. The results obtained indicate that the NIR technology can be very efficient and low cost to test the viability of corn seeds regardless of the variety to which they belong, and that what is really important are the techniques of conservation and storage under appropriate conditions of temperature and relative humidity (RH).
Dentro de la producción mundial de granos y cereales (arroz, trigo, cebada, etc.) el maíz (Zea mays L.) representa el 40%, países como Estados Unidos (37%) y China (23%) son los de mayor producción de grano con rendimientos de 10 y 6 t/ha respectivamente. Ecuador se encuentra dentro de los 50 principales productores mundiales de este, siendo un cultivo de alta transcendencia se produce en 21 de las 24 provincias lo cual su producción se concentra en las provincias de Los Ríos, Guayas, Manabí y Loja, la importancia de la presente investigación radica en la escasa investigación que genere información de cómo debemos conservar nuestras semillas sin que pierdan su viabilidad y vigor genético, así como de programas de fitomejoramiento que generen variabilidad genética de características agronómicas superiores. La presente investigación se la realizó en la Granja Experimental “Santa Inés” perteneciente a la Unidad Académica de Ciencias Agropecuarias de la Universidad Técnica de Machala (UTMACH), ubicada en la Parroquia El Cambio, Cantón Machala. Siendo el objetivo: evaluar el porcentaje de viabilidad y germinación de semillas de maíz mediante pruebas de tetrazolio y espectroscopia de infrarrojo (FT-NIR). Para la realización del trabajo experimental se realizó completamente al azar, utilizando nueve accesiones con dos factores de estudio (métodos de evaluación de viabilidad (Tetrazolio y NIR) y variedad) con 3 repeticiones. Se realizó pruebas de viabilidad en laboratorio utilizando un artefacto NIR SCIO para escanear las semillas antes de ponerlas a germinar generando una curva de absorbancia de cada semillas, luego se colocan las mismas semillas a germinación y usando el método del Tetrazolio se observa la tinción del embrión de cada semilla, las lecturas se lo realizan después de las 24 horas, los datos obtenidos en laboratorio fueron sometidos a una prueba estadística Análisis de Varianza Factorial y Tukey al 0,05 mediante el programa Statistical Pasckage of the Social Sciences (SPSS). Entre los dos métodos, el de menor costo, sin destruir la semilla y de fácil manipulación mediante un teléfono inteligente es el NIR, logrando resultados 100% positivos en cuanto a viabilidad y vigor de semillas; el método del Tetrazolio es una prueba confiable que de igual forma tiene resultados efectivos pero el costo es superior y sobre todo destruye a la semilla para realizar la evaluación. De los resultados conseguidos se determinó que no existe diferencia significativa entre variedades de maíz de acuerdo a su tiempo de almacenamiento el cual éste medio no influyó. Las variedades V1A, V2A, V3A que contienen un nivel de humedad de 5.5% presentaron menos viabilidad en cuanto a las variedades V1B, V2B, V3B, V1C, V2C, V3C que obtuvieron menor humedad (5%), pero sí mayor porcentaje de viabilidad. El método del tetrazolio presento una media de 67,11 y en el método NIR una media de 68,15 por lo que no existe diferencias significativas entre los dos métodos. Los resultados obtenidos señalan que la tecnología NIR puede resultar muy eficiente y de bajos costo para testear la viabilidad de semillas de maíz independientemente de la variedad a las que pertenezcan, y que lo realmente importante son las técnicas de conservación y almacenamiento en condiciones adecuadas de temperatura y humedad relativa (HR).
Keywords: GERMOPLASMA; VIABILIDAD; CULTIVARES; MAÍZ